Dividend yield as an investment strategy: Evidence from the Finnish stock market : Dogs of the Dow - Korkiamäki, Jaro (My University, 2020)
Investment based strategies have been extensively studied and strategies have a deep interest. Dividend based investment strategies is a form of value investing and include strategies such as Dogs of the Dow (DOD), which was firstly introduced in 1988 by John Slatter. DOD strategy is choosing a portfolio consisting of 10 stocks with the highest dividend yield. The DOD strategy has been found to have abnormal market-adjusted returns. However, the results are mixed as some studies provide opposite results. Moreover, after adjusting return after taxes and transaction costs, the return lower - many studies find, that after the tax and transaction costs adjustments, the economic significance declines. In contrast to the portfolio theory, the DOD strategy does not form the best possible portfolio with respect to the risk and return trade-off. The DOD strategy should have a higher systematic risk, as the portfolio is not well diversified. Dividend provides essential information about the company. The dividend distribution is informative and an increase in the dividend is a signal to investors that the management of the company is positive about the company's future performance. Based on theory, the dividend distribution is not relevant if the investor is rational. The increase in wealth is the same, whether it comes in a form of dividend or as an increase in the stock's price. This thesis study the effectiveness of the DOD strategy being applied on the Finnish stock markets on a sample period of 2001-2017. The method follows the standard DOD portfolio procedure. The data is mostly gathered from the NASDAQ Helsinki, the dividend distributed gathered from the company's webpages. The performance of the Dogs of the Dow portfolio is measured in two ways. In terms of log returns and risk-adjusted returns, measured by Sharpe ratio and Treynor Ratio. The empirical findings do not find support that the DOD strategy is outperforming the main benchmark index, OMXH 25 GI. The benchmark index is Helsinki stock exchange index of 25 most traded stocks and the index also takes dividends. The study however, support that the DOD-10 has higher risk- adjusted returns than the benchmark index OMXH25 GI. The results indicate that more research is required to find consensus on the Dogs of the Dow investment strategy.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance